Effects of demographic factors on provision of feedback in postgraduate medical education - Bagwandeen, C.I.; Singaram, V.S. (South African Journal of Higher Education, 2018)
A key element in the process of clinical medical education is the process of providing feedback by comparing the directly observed performance of postgraduate doctors training to become specialists to that of a previously identified and communicated ‘gold standard’ and incorporating a plan for improvement. This is regarded as crucial to enhance clinical competencies. Hence, a greater understanding of the clinical educational environment and the various factors that impact on the giving and receiving of feedback within such a setting is required. A mixed methods approach was adopted for this observational study regarding the perceptions of the quality of feedback given and received at a large multicultural teaching hospital. Relationships between demographics and certain important aspects of the provision of feedback were observed which impact on the context in which feedback is given and received. The study found that appropriate strategies should be implemented to improve teaching capacity of consultants, together with gender empowerment and academic support programmes for registrars.